2002
DOI: 10.1126/science.1068356
|View full text |Cite
|
Sign up to set email alerts
|

Coordination of PIC Assembly and Chromatin Remodeling During Differentiation-Induced Gene Activation

Abstract: We analyzed the ordered recruitment of factors to the human alpha1 antitrypsin promoter around the initial activation of the gene during enterocyte differentiation. We found that a complete preinitiation complex, including phosphorylated RNA pol II, was assembled at the promoter long before transcriptional activation. The histone acetyltransferases CBP and P/CAF were recruited subsequently, but local histone hyperacetylation was delayed. After transient recruitment of the human Brahma homolog hBrm, remodeling … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
246
2
5

Year Published

2003
2003
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 293 publications
(263 citation statements)
references
References 26 publications
10
246
2
5
Order By: Relevance
“…Blocking Brg1 or SWI/SNF activity interferes with differentiation in retinal, myeloid, muscle, adipocyte, enterocyte, erythrocyte and neuronal cells. 31,[74][75][76][77][78][79][80] Together, the observations above suggest that the antagonistic interactions between Geminin and SWI/SNF that we have observed during neurogenesis could also regulate the proliferative-differentiative transition in other cellular contexts. Effects of both Geminin and SWI/SNF in regulating the proliferation to differentiation transition intersect with many other critical cell cycle and transcriptional control systems in a complex manner.…”
Section: Geminin Swi/snf and Regulation Of The Cell Proliferation-dmentioning
confidence: 72%
“…Blocking Brg1 or SWI/SNF activity interferes with differentiation in retinal, myeloid, muscle, adipocyte, enterocyte, erythrocyte and neuronal cells. 31,[74][75][76][77][78][79][80] Together, the observations above suggest that the antagonistic interactions between Geminin and SWI/SNF that we have observed during neurogenesis could also regulate the proliferative-differentiative transition in other cellular contexts. Effects of both Geminin and SWI/SNF in regulating the proliferation to differentiation transition intersect with many other critical cell cycle and transcriptional control systems in a complex manner.…”
Section: Geminin Swi/snf and Regulation Of The Cell Proliferation-dmentioning
confidence: 72%
“…Upon activation by heat shock, Pol II is able to rapidly transcribe these genes. Regulation of Pol II activity after recruitment has also been described in bacteria 23 , yeast 13 and mammalian cell lines 3,[6][7][8][9][10][11][12] , and includes instances where Pol II is found in an inactive pre-initiation complex 24,25 . We will collectively refer to inactive Pol II near the transcription start site as stalled Pol II.…”
Section: Introductionmentioning
confidence: 96%
“…Also, GTFs bind to Drosophila promoters that are repressed by Polycomb group proteins (Breiling et al 2001). It has been shown that chromatin remodeling of the ␣1-antitrypsin gene promoter occurs after PIC assembly (Soutoglou and Talianidis 2002), and that elongation is the rate-limiting step in the regulation of many genes, including c-myc (Bentley and Groudine 1986;Krumm et al 1992), c-fos (Plet et al 1995), heat-shock protein (Brown et al 1996;Lis 1998), and transcription regulated by the HIV-1 LTR (Marciniak and Sharp 1991; for review, see Jones and Peterlin 1994). These observations demonstrate that events downstream of PIC assembly can be rate-limiting steps in transcription, and may represent common mechanisms for establishing an active state in many genes.…”
Section: Relationship Between Expression Levels and Pic Assemblymentioning
confidence: 99%